Impact of the spatial congruence of redundant targets on within-modal and cross-modal integration - Girard, S.; Pelland, M.; Lepore, F.; Collignon, O. (Experimental brain research, 2013)
Although the topic of sensory integration has raised increasing interest, the differing behavioral outcome of combining unisensory versus multisensory inputs has surprisingly only been scarcely investigated. In the present experiment, observers were required to respond as fast as possible to (1) lateralized visual or tactile targets presented alone, (2) double stimulation within the same modality or (3) double stimulation across modalities. Each combination was either delivered within the same hemispace (spatially aligned) or in different hemispaces (spatially misaligned). Results show that the redundancy gains (RG) obtained from the cross-modal conditions were far greater than those obtained from combinations of two visual or two tactile targets. Consistently, we observed that the reaction time distributions of cross-modal targets, but not those of within-modal targets, surpass the predicted reaction time distribution based on the summed probability distributions of each constituent stimulus presented alone. Moreover, we found that the spatial alignment of the targets did not influence the RG obtained in cross-modal conditions, whereas within-modal stimuli produced a greater RG when the targets where delivered in separate hemispaces. These results suggest that within-modal and cross-modal integration are not only distinguishable by the amount of facilitation they produce, but also by the spatial configuration under which this facilitation occurs. Our study strongly supports the notion that estimates of the same event that are more independent produce enhanced integrative gains.